Compact microstrip lowpass filter with wide stopband and very‐sharp roll‐off. Issue 10 (1st May 2016) - Hayati, M.; Akbari, M.; Salahi, R.
Abstract : A novel microstrip lowpass filter (LPF) with good specifications such as wide stopband and sharp roll‐off is reported. The filter structure consists of split ring resonator loaded by folded polygene patches. The proposed filter with −3 dB cut‐off frequency at 1.57 GHz has been designed, fabricated and measured. The LPF has a wide stopband from 1.67 to 14 GHz with a rejection level greater than −20 dB, sharp roll‐off rate equal to 170 dB/GHz and low insertion loss lower than 0.13 dB in 94% of the passband. Finally, a high figure of merit of 51, 178 is obtained.